2008
DOI: 10.1159/000118662
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Disinfectants Used in Cooling Towers against <i>Legionella pneumophila</i>

Abstract: Background:Legionella persists in man-made aquatic installations despite preventive treatments. More information about disinfectants could improve the effectiveness of treatments. This study tests the susceptibility of Legionella pneumophila serogroup (sg) 1 against 8 disinfectants used in cooling tower treatments. Methods: We determined the minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC) and bactericidal effect of sodium hypochlorite (A), hydrogen peroxide with silver nitrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…DDAC is a Quaternary Ammonium Compound (QAC) disinfectant often used in the industry to disinfect hard surfaces because of its relatively low toxicity, broad antimicrobial spectrum, non-volatility, and chemical stability [28]. In a previous study, the disinfectant DDAC showed the bactericidal activity against L. pneumophila at concentrations used in cooling tower treatments [29]. In addition, the DDAC is a membrane-active agent and causes membrane leakage of intracellular material [30].…”
Section: Discussionmentioning
confidence: 99%
“…DDAC is a Quaternary Ammonium Compound (QAC) disinfectant often used in the industry to disinfect hard surfaces because of its relatively low toxicity, broad antimicrobial spectrum, non-volatility, and chemical stability [28]. In a previous study, the disinfectant DDAC showed the bactericidal activity against L. pneumophila at concentrations used in cooling tower treatments [29]. In addition, the DDAC is a membrane-active agent and causes membrane leakage of intracellular material [30].…”
Section: Discussionmentioning
confidence: 99%
“…Used appropriately, biocides offer an important means of reducing the transmission and growth of microorganisms (34)(35)(36). They have the potential, through disinfection and antisepsis, to reduce the incidence of infections and the burden on antibiotics (35,37) and to protect consumers through the preservation of liquid formulations (38).…”
Section: Discussionmentioning
confidence: 99%
“…Legionella are not completely eliminated from drinking water by standard water treatment practices. For example, Legionella are comparatively more resistant to chlorine than Escherichia coli ( Garcia and Pelaz 2008 ; Hosein et al 2005 ; Kim et al 2002 ; Zhang et al 2007 ). Legionella are also known to be sheltered within encysted amoebae; indeed, after phagocytosis by amoebae, whose cells are relatively chlorine-resistant, Legionella can survive up to 50 ppm chlorine ( Kilvington and Price 1990 ).…”
Section: Legionella Ecologymentioning
confidence: 99%